2014
DOI: 10.1016/j.snb.2013.11.088
|View full text |Cite
|
Sign up to set email alerts
|

Metal oxide based multisensor array and portable database for field analysis of antioxidants

Abstract: We report a novel chemical sensing array based on metal oxide nanoparticles as a portable and inexpensive paper-based colorimetric method for polyphenol detection and field characterization of antioxidant containing samples. Multiple metal oxide nanoparticles with various polyphenol binding properties were used as active sensing materials to develop the sensor array and establish a database of polyphenol standards that include epigallocatechin gallate, gallic acid, resveratrol, and Trolox among others. Unique … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 37 publications
(38 reference statements)
2
34
0
Order By: Relevance
“…An electrophoretic mobility assay suggested that the binding of oxides stems from electrostatic attraction, since the oxides were negatively charged under the experimental conditions, in line with previous reports, whereas the nanofibers were positively charged (Figure d). The peptide nanofibers therefore appear useful for the immobilization of oxide materials, as required in various applications . Additionally, in relation to native GS T4P, the results are congruent with a previous study, which reported the enhancement of early bacterial attachment to Fe(III) oxide surfaces after denying a negatively charged post‐translational tyrosine modification in the C‐terminal region of GS pilin …”
Section: Methodssupporting
confidence: 88%
“…An electrophoretic mobility assay suggested that the binding of oxides stems from electrostatic attraction, since the oxides were negatively charged under the experimental conditions, in line with previous reports, whereas the nanofibers were positively charged (Figure d). The peptide nanofibers therefore appear useful for the immobilization of oxide materials, as required in various applications . Additionally, in relation to native GS T4P, the results are congruent with a previous study, which reported the enhancement of early bacterial attachment to Fe(III) oxide surfaces after denying a negatively charged post‐translational tyrosine modification in the C‐terminal region of GS pilin …”
Section: Methodssupporting
confidence: 88%
“…Students can create their own sensors within an hour. 3,14 The procedure involves dipping the filter paper in 4% nanoceria dispersed in 0.5% acetic acid and allowing it to dry. 15 At the undergraduate level, as a prelaboratory assignment, students should be expected to carry out a literature review, allowing them to investigate the role of antioxidants in human health, as well as methods used for their detection.…”
Section: ■ Experiments Overviewmentioning
confidence: 99%
“…47 Evans et al 48 modified μPADs with SiO2NPs to improve color intensity and uniformity of a colorimetric device applied to three different enzymatic reactions with clinical relevance (lactate, glucose, and glutamate). Sharpe et al developed novel chemical sensing arrays based on redox active metal oxide NPs as a portable and inexpensive paper-based colorimetric method for polyphenol detection 49 and field characterization of antioxidant containing samples 27 ( Fig. 5).…”
Section: ·2 Modification Of Cellulose Papermentioning
confidence: 99%
“…Adsorption of the antioxidants onto the particle surface caused a unique colorimetric response due to formation of charge transfer complexes that vary in color and intensity with the chemical structure of the antioxidants. 107 Li et al monitored production of amines, as products of fish degradation, using PANI:PSS composites which change from white to purple at pH 11 because of the release of amines. Eventually this chemistry could be used as freshness indicators for seafood.…”
Section: ·3 Food Safety Monitoringmentioning
confidence: 99%